2016
DOI: 10.1002/hep.28499
|View full text |Cite
|
Sign up to set email alerts
|

Recurrent recessive mutation in deoxyguanosine kinase causes idiopathic noncirrhotic portal hypertension

Abstract: Despite advances in the diagnosis and management of idiopathic non-cirrhotic portal hypertension (INCPH), its pathogenesis remains elusive. Insight may be gained from study of early onset familial INCPH, in which Mendelian mutations may account for disease. We performed exome sequencing of 8 subjects from 6 kindreds with onset of portal hypertension of indeterminate etiology during infancy or childhood. Three subjects from two consanguineous families shared the identical rare homozygous p.N46S mutation in DGUO… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
44
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 59 publications
(46 citation statements)
references
References 32 publications
2
44
0
Order By: Relevance
“…Human leukocyte antigen DR3 + was identified in 7 out of 8 patients with IPH belonging to four different families with more than one member affected . Other gene mutations are present in other patients with IPH and familiar aggregation such as mutations in the telomerase complex gene, autosomal dominantly inherited mutations in the potassium/calcium‐activated channel subfamily N member 3 gene, and recessively inherited mutations in the deoxyguanosine kinase gene …”
Section: Pathophysiology Etiology and Risk Factorsmentioning
confidence: 99%
“…Human leukocyte antigen DR3 + was identified in 7 out of 8 patients with IPH belonging to four different families with more than one member affected . Other gene mutations are present in other patients with IPH and familiar aggregation such as mutations in the telomerase complex gene, autosomal dominantly inherited mutations in the potassium/calcium‐activated channel subfamily N member 3 gene, and recessively inherited mutations in the deoxyguanosine kinase gene …”
Section: Pathophysiology Etiology and Risk Factorsmentioning
confidence: 99%
“…One example of an unmet medical need is idiopathic liver disease, which remains a challenge in both pediatric and adult hepatology. We and others have shown the utility of whole-exome sequencing in the diagnosis of such patients (2)(3)(4)(5)(6). Children with unexplained liver disease who are the offspring of a consanguineous union are excellent candidates for recessive disease-causing mutations.…”
mentioning
confidence: 99%
“…Other independent studies have consistently reported WES diagnostic rates of 20% or higher . Furthermore, we and others have successfully combined WES with deep phenotyping (i.e., detailed characterization of each patient's phenotypic features) to identify the underlying genetic defects in infants and children with idiopathic liver diseases, including children with liver failure of indeterminate etiology . Astute clinical annotation (i.e., comprehensive phenotype description of the patient) is central to harnessing the maximal potential of genomic data .…”
Section: Where Could Hepatologists Be Missing Liver‐related Genetic Tmentioning
confidence: 95%